A Crystalline Iron Terminal Methylidene - Aghazada, Sadig; Munz, Dominik; Heinemann, Frank Wilhelm; Scheurer, Andreas; Meyer, Karsten (Journal of the American Chemical Society, 2021)
Iron methylidene species are alleged intermediates in the Fischer-Tropsch process and in olefin cyclopropanation, yet iron methylidene complexes with unambiguously established molecular and electronic structures remain elusive. In this study, we characterize an iron terminal methylidene complex by single-crystal X-ray diffractometry (scXRD), CHN combustion elemental analysis, 1H/13C/31P/1H-13C NMR, and zero-field 57Fe Mössbauer spectroscopy and study its reactivity. A series of closely related complexes in different oxidation states were synthesized, isolated and characterized in order to validate the electronic structure of the title methylidene complex. The computational analysis substantiates the proposed Fischer-type electronic description while emphasizing high Fe=CH2 bond covalency, considerable double bond order, and thus, substantial alkylidene character.
CRIS-Team Scopus Importer:2021-10-29

A Terminal Iron Nitrilimine Complex: Accessing the Terminal Nitride through Diazo N−N Bond Cleavage - Aghazada, Sadig; Miehlich, Matthias; Messelberger, Julian; Heinemann, Frank Wilhelm; Munz, Dominik; Meyer, Karsten (Angewandte Chemie International Edition, 2019)
A novel method for the N−N bond cleavage of trimethylsilyl diazomethane is reported for the synthesis of terminal nitride complexes. The lithium salt of trimethylsilyl diazomethane was used to generate a rare terminal nitrilimine transition metal complex with partially occupied d-orbitals. This iron complex 2 was characterized by CHN combustion analysis, 1H and 13C NMR spectroscopic analysis, single-crystal X-ray crystallography, SQUID magnetometry, 57Fe Mössbauer spectroscopy, and computational analysis. The combined results suggest a high-spin d 6 (S=2) electronic configuration and an allenic structure of the nitrilimine ligand. Reduction of 2 results in release of the nitrilimine ligand and formation of the iron(I) complex 3, which was characterized by CHN combustion analysis, 1H NMR spectroscopic analysis, and single-crystal X-ray crystallography. Treatment of 2 with fluoride salts quantitatively yields the diamagnetic FeIV nitride complex 4, with concomitant formation of cyanide and trimethylsilyl fluoride through N−N bond cleavage.
CRIS-Team Scopus Importer:2019-11-15
Keywords: diazo compounds; iron; N-heterocyclic carbenes; N−N activation; terminal nitrides

Cobalt Diazo-Compounds: From Nitrilimide to Isocyanoamide via a Diazomethanediide Fleeting Intermediate - Aghazada, Sadig; Fehn, Dominik; Heinemann, Frank Wilhelm; Munz, Dominik; Meyer, Karsten (Angewandte Chemie International Edition, 2021)
Lithium trimethylsilyldiazomethanide and a cobalt (II) precursor with an N-anchored tris-NHC (TIMENmes) ligand provide access to the cobalt nitrilimide 1. Complex 1 was structurally characterized by single-crystal X-ray diffractometry (SC-XRD) and its electronic structure was examined in detail, including EPR spectroscopy, SQUID magnetometry and computational analyses. The desilylation of the C-(trimethylsilyl)nitrilimide reveals a transient complex with an elusive diazomethanediide ligand, which substitutes one of the mesitylene rings of the ancillary ligand through C-N bond cleavage. This transformation results in the cyclometalated cobalt(II) complex 2, featuring a rare isocyanoamido-kappa-C ligand.
CRIS-Team WoS Importer:2021-04-16

Discerning recombination mechanisms and ideality factors through impedance analysis of high-efficiency perovskite solar cells - Almora, Osbel; Cho, Kyung Taek; Aghazada, Sadig; Zimmermann, Iwan; Matt, Gebhard; Brabec, Christoph; Nazeeruddin, Mohammad Khaja; Garcia-Belmonte, Germa (Nano Energy, 2018)
The ubiquitous hysteresis in the current-voltage characteristic of perovskite solar cells (PSCs) interferes in a proper determination of the diode ideality factor (n), a key parameter commonly adopted to analyze recombination mechanisms. An alternative way of determining n is by measuring the voltage variation of the ac resistances in conditions of negligible steady-state dc currents. A reliable analysis of n based on the determination of the resistive response, free of hysteretic influences, reveals two separated voltage exponential dependences using different perovskite absorbers (3D perovskites layer based on CH3NH3PbI3 or mixed Cs(0.1)FA(0.74)MA(0.13)PbI(2.48)Br(0.39)) and a variety of interlayers (2D perovskite thin capping). The dominant resistive element always exhibits an exponential dependence with factor n approximate to 2, irrespective of the type of perovskite and capping layers. In addition, a non-negligible resistive mechanism occurs at low-frequencies (with voltage-independent time constant similar to 1 s) which is related to the kinetic properties of the outer interfaces, with varying ideality factor (n = 2 for CH3NH3PbI3, and n = 1.5 for Cs(0.1)FA(0.74)MA(0.13)PbI(2.48)Br(0.39)). Our work identifies common features in the carrier recombination mechanisms among different types of high-efficiency PSCs, and simultaneously signals particularities on specific architectures, mostly in the carrier dynamics at outer interfaces.
Keywords: Perovskites solar cells; Recombination; Impedance spectroscopy; Capacitance; 2D capping

Iron-Catalyzed Olefin Metathesis: Recent Theoretical and Experimental Advances - Grau, Benedikt; Neuhauser, Alexander; Aghazada, Sadig; Meyer, Karsten; Tsogoeva, Svetlana (Chemistry - A European Journal, 2022)
The "metathesis reaction" is a straightforward and often metal-catalyzed chemical reaction that transforms two hydrocarbon molecules to two new hydrocarbons by exchange of molecular fragments. Alkane, alkene and alkyne metathesis have become an important tool in synthetic chemistry and have provided access to complex organic structures. Since the discovery of industrial olefin metathesis in the 1960s, many modifications have been reported; thus, increasing scope and improving reaction selectivity. Olefin metathesis catalysts based on high-valent group six elements or Ru(IV) have been developed and improved through ligand modifications. In addition, significant effort was invested to realize olefin metathesis with a non-toxic, bio-compatible and one of the most abundant elements in the earth ' s crust; namely, iron. First evidences suggest that low-valent Fe(II) complexes are active in olefin metathesis. Although the latter has not been unambiguously established, this review summarizes the key advances in the field and aims to guide through the challenges.
CRIS-Team WoS Importer:2022-09-16